The Role of Government and the Community in the Development of Morea Pond Tourism in Larike Village, West Leihitu District, Central Maluku Regency - Kalsum Consina; Aholiab Watloly; Prapti Murwani (Westscience Press, 2023)
Tourism holds significant potential as an economic revenue source and a driver of development in regions. One of the tourist destinations with the potential for continuous development in the eastern part of Indonesia is the Morea Pond tourism destination in Larike Village, West Leihitu District, Central Maluku Regency. This research aims to analyze the roles of the government and the community in the efforts to develop the tourism destination in the Maluku Province. The research methodology employs a qualitative approach with data collection techniques including in-depth interviews, participatory observation, and document analysis. The findings reveal that the government plays a role as a facilitator, motivator, and educator in promoting the development of Morea Pond tourism. This involves providing information and creating a conducive tourism climate, offering facilities to support the development of tourism potential, and educating the community through tourism-related training. The government also maintains environmental conservation, ensures order and security, and enhances the beauty of the tourist location. Additionally, the community contributes to the development of the Morea Pond tourism site by cultivating entrepreneurial skills such as culinary businesses, participating in tourism training to provide services for tourists, and serving as guides in performances at the Morea Pond tourism location.